Respon Dua Varietas Tanaman Kentang (Solanum tuerosum L.) Terhadap Aplikasi Pupuk Majemuk NPK - Dian Nitami Quraisyin; Sugiarto Sugiarto; Nurhidayati Nurhidayati (Folium : Jurnal Ilmu Pertanian, 2020)
Demand for potatoes from time to time is increasing. Therefore it is necessary to increase the productivity of potatoes through appropriate cultivation techniques especially in new potato varieties. This study aims to determine the effect of NPK (16:16:16) fertilizer dosage on the growth and yield of two potato varieties in the highlands.The design used was factorial Randomized Block Design (RAK) using 2 factors. The first factor was the aplication of NPK fertilizer with 3 levels, namely P0 = without fertilizer, P1 = 400 kg fertilizer NPK ha-1  and P2 = 800 kg NPK fertilizer ha-1. The second factor is the type of variety with 2 levels, V1 = Granola L and V2 = Granolla Arjuno. Of these two factors, there were six treatment, Each treatment was repeated 3 times. There are two observed variables which are growth variables (plant height, number of stems, number of leaves and stem diameter) and yield variables (number of tubers,  weight of , tuber per plot and per hectare). The data collected was analyzed based on F Test at the level of 5% and LSD test 5%. The results showed that the best plant growth was Granolla Arjuno variety with a dose of NPK fertilizer 400 kg ha-1 (P1V2). While the treatment that gives the highest results is Granolla Arjuno variety with a dose of N-P-K fertilizer 400 kg ha-1 (P1V2)